Acceptance of pharmacist-led stewardship recommendations for patients with community-acquired pneumonia - Ramara E. Walker; Rebecca Schulte; Andrea M. Pallotta; Larisa G. Tereshchenko; Victoria A. Criswell; Abhishek Deshpande; Michael B. Rothberg (Cambridge University Press, 2024)
Abstract Background: Community-acquired pneumonia (CAP) is a leading cause of hospitalizations and mortality in the US. Overuse of extended spectrum antibiotics (ESA) for CAP contributes to antimicrobial resistance. The 2019 Infectious Diseases Society of America/American Thoracic Society CAP guidelines emphasize de-escalation of ESA following negative cultures, early switch to oral (PO) antibiotics, and limited duration of therapy (DOT). This study describes clinicians' acceptance of an infectious diseases-trained (ID) pharmacist-led stewardship recommendations in hospitalized patients with CAP. Methods: This prospective, single-arm, cohort study included adults admitted with a diagnosis of pneumonia to six Cleveland Clinic hospitals receiving ID pharmacist-led stewardship recommendations. The ID pharmacist provided recommendations for ESA de-escalation, DOT, intravenous (IV) to PO transition, and antimicrobial discontinuation. Descriptive statistics were used to describe clinician acceptance rates. Results: From November 1, 2022, to January 31, 2024, the ID pharmacist made recommendations for 685 patient encounters to 327 clinicians. Of these patients, 52% received an ESA and 15% had severe CAP. There were 959 recommendations: ESA de-escalation (19%), DOT (46%), IV to PO transition (19%), antimicrobial discontinuation (13%), and other (3%). Clinicians accepted 693 recommendations (72%): IV to PO transition (148/184, 80%), ESA de-escalation (141/181 78%), antimicrobial discontinuation (94/128, 73%), DOT (286/437, 65%), and other (24/29, 83%). Conclusion: Clinicians were generally receptive to ID pharmacist-led CAP recommendations with an overall acceptance rate of 72%. Prescribers were most receptive to recommendations for IV to PO conversion and least receptive to limiting DOT.